h(t) = t^{2} + 5t; t = −1, t = 2

af(z) = 5 − 4z^{2}; z = −2, z = 0

f(x) = x^{3} − 5x^{2}; x = 0, x = 10

f(x) = x + x^{4}; x = −3, x = 5

f(x) = 5x^{2}; x = 3, x = 3 + h

f(x) = 3 − x^{2}; x = 6, x = 6 + h

[4+5-(1-5)]/3 = 13/3

[5-(5-16)]/2 =8

[1000-500-0]/10 =50

[5+625+3-81]/8 = (633-81)/8 = 552/8 = 69

[5(3+h)^2-5(3)^2]/h = 5(9+6h+h^2-9)/h = 5*6+5h = 30+5h

[3-(6+h)^2-3+6^2]/h = -(36+12h+h^2-36)/h = -12-h

Secure Information

Content will be erased after question is completed.

Enter the email address associated with your account, and we will email you a link to reset your password.

Forgot your password?

Sign Up